Challenges and dilemmas on universal coverage for non-communicable diseases in middle-income countries: evidence and lessons from Mexico - Armando Arredondo; Alejandra Azar; Ana Lucia Recaman (BMC, 2018)
Abstract Background Despite more than 20 years of reform projects in health systems, the universal coverage strategy has not reached the expected results in most middle-income countries (MICs). Using evidence from the Mexican case on diabetes and hypertension as tracers of non-communicable diseases, the effective coverage rate barely surpasses half of the expected goals necessary to meet the challenges that these two diseases represent at the population level. Prevalence and incidence rates do not diminish either; they even grow. In terms of the economic burden, this means that lack of financial protection and catastrophic expense rates have increased, contrary to what could have been expected. Discussion As any complex system, health systems present challenges and dilemmas that are difficult to solve. In terms of universal coverage, when contrasting normative coverage versus effective coverage, the epidemiological, cultural, organizational and economic challenges and barriers become evident. Such challenges have not allowed a greater effectiveness of the contributions of state of the art medicine in the resolution of health problems, particularly in relation to diabetes and hypertension. Conclusions Despite of the existence of many universal coverage projects, strategies and programs implemented in MICs, challenges remain and, far from disappearing, unresolved problems are still present, even with increasing trends. The model of care based on a curative biomedical approach was enough to respond to the health needs of the last century, but is no longer adapted to the needs of the present century. The dilemmas of continuity vs. rupture require to review and discuss the background and structure of health systems and their underlying models of care. These two elements have not allowed the different coverage schemes to guarantee greater effectiveness in the application of state of the art medicine, nor a greater health care financial protection for patients and their families. We thus can either accept the fragmented health systems and bio-medical-curative models of care approach or, instead, we can move towards integrated health systems that would be based on a socio-medical-preventive approach to health care.